Emergence of a Plant Pathogen in Europe Associated with Multiple Intercontinental Introductions - Landa, Blanca B. (Appl Environ Microbiol, 2020)
Pathogen introductions have led to numerous disease outbreaks in naive regions of the globe. The plant pathogen Xylella fastidiosa has been associated with various recent epidemics in Europe affecting agricultural crops, such as almond, grapevine, and olive, but also endemic species occurring in natural forest landscapes and ornamental plants. We compared whole-genome sequences of X. fastidiosa subspecies multiplex from America and strains associated with recent outbreaks in southern Europe to infer their likely origins and paths of introduction within and between the two continents. Phylogenetic analyses indicated multiple introductions of X. fastidiosa subspecies multiplex into Italy, Spain, and France, most of which emerged from a clade with limited genetic diversity with a likely origin in California, USA. The limited genetic diversity observed in X. fastidiosa subspecies multiplex strains originating from California is likely due to the clade itself being an introduction from X. fastidiosa subspecies multiplex populations in the southeastern United States, where this subspecies is most likely endemic. Despite the genetic diversity found in some areas in Europe, there was no clear evidence of recombination occurring among introduced X. fastidiosa strains in Europe. Sequence type taxonomy, based on multilocus sequence typing (MLST), was shown, at least in one case, to not lead to monophyletic clades of this pathogen; whole-genome sequence data were more informative in resolving the history of introductions than MLST data. Although additional data are necessary to carefully tease out the paths of these recent dispersal events, our results indicate that whole-genome sequence data should be considered when developing management strategies for X. fastidiosa outbreaks. IMPORTANCE Xylella fastidiosa is an economically important plant-pathogenic bacterium that has emerged as a pathogen of global importance associated with a devastating epidemic in olive trees in Italy associated with X. fastidiosa subspecies pauca and other outbreaks in Europe, such as X. fastidiosa subspecies fastidiosa and X. fastidiosa subspecies multiplex in Spain and X. fastidiosa subspecies multiplex in France. We present evidence of multiple introductions of X. fastidiosa subspecies multiplex, likely from the United States, into Spain, Italy, and France. These introductions illustrate the risks associated with the commercial trade of plant material at global scales and the need to develop effective policy to limit the likelihood of pathogen pollution into naive regions. Our study demonstrates the need to utilize whole-genome sequence data to study X. fastidiosa introductions at outbreak stages, since a limited number of genetic markers does not provide sufficient phylogenetic resolution to determine dispersal paths or relationships among strains that are of biological and quarantine relevance.